Detection of multiple sclerosis using deep learning - Jannat, Sabila Al; Hoque, Tanjina; Supti, Nafisa Alam (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.